Assessing functioning for individuals with neurodevelopmental conditions: Current clinical practice in Australia. (7th August 2022) - D'Arcy, Emily; Evans, Kiah; Afsharnejad, Bahareh; Milbourn, Benjamin; Bölte, Sven; Girdler, Sonya
Abstract: Background: In the disability sector globally, and specifically in Australia, assessments of functioning have become key to diagnostic processes, and accessing therapy and funding. Over half of all individuals accessing support through Australia's National Disability Insurance Scheme have a neurodevelopmental condition diagnosis. Little is known about assessments of functioning for this population. Methods: A mixed methods online survey was designed to understand the current assessment of functioning practices (including clinical contexts, concepts being assessed, and assessment methods) and barriers and facilitators to clinicians using best practice. Results were analysed descriptively, and differences between professions calculated where possible. Content analysis was used to explore qualitative comments. Results: Clinicians from various medical and allied health backgrounds completed the survey ( n = 93), with varying ranges of age, experience, and education. Clinicians reported that they assessed functioning across age, setting, sector, funding body, and individuals with a wide variety of diagnoses. Missing from current practice is a clear transdisciplinary conceptualisation of functioning. The largest barriers to best practice were limited time, large caseloads, availability of appropriate tools, and lack of clarity from funding bodies. Conclusions: Missing from current practice is a clear transdisciplinary conceptualisation of functioning.These results will help inform steps forward to improve assessment of functioning practices to ensure that all individuals receive appropriate and sufficient support.